Pengaruh Degradasi Lahan Terhadap Keberlanjutan Pertanian Padi di Indonesia Hasil Survei Pertanian Terintegrasi (SITASI) 2021 - Putri, Fitriani Aditya (Seminar Nasional Official Statistics, 2024)
In realizing sustainable development in accordance with the second pillar of the 2045 Golden Indonesia Development related to food security and environmental stability, the current and future agricultural sector is faced with various challenges, one of which is land degradation. Land degradation can threaten agriculture in Indonesia. This study aims to examine the impact of land degradation on the sustainability of paddy farming in Indonesia. Based on data from the 2021 Integrated Agricultural Survey (SITASI), estimation results using multiple linear regression show that land degradation has an effect on paddy production in Indonesia. Land degradation in the form of soil erosion, soil infertility, and salinity of irrigated land can actually reduce paddy production in Indonesia. Therefore, the government's role is very important in preventing land degradation in Indonesia, such as implementing an environmentally friendly organic farming system and increasing the role of agricultural institutions. The hope is that agricultural land degradation can be prevented in order to maintain the sustainability of paddy farming in Indonesia in realizing food security by 2045.